EXTRACTION, PURIFICATION AND CHARACTERIZATION OF CYTOSINE DEAMINASE FROM Saccharomyces cerevisiae - Nader, Mohammed; Al-Maeny, Safaa (Iraqi Journal of Science, 2024)
The cytosine deaminase was extracted by using organic solvent toluene and the value of specific activity of crude extract was (9.6) mu/mg protein . The enzyme was purified in few steps including precipitating the enzyme by using ammonium sulfate at defferent saturation percent, The optimum percent was 60% saturation percent which gave value of specfic activity of (12.5) mu/mg protein fold of purification was (1.302) times and the yield was 4.82% . Then the enzume solution was passed through DEAE – cellulose column chromatography. The peaks was collected and the value of specific activity was measured which was (358) mu/mg protein, fold of purification was (37.29) times, and the yield was (2.55)%.The enzyme solution was concentrated and passed through sephadex G-200 gelfilteration and the value of specific activity was (400) mu/mg protein, fold purification (41.66) times and yeid was 1.19%.